Self Control And Peer Attachment: Unraveling Their Links to Adolescent Cybersex Behavior - Septiraningrum, Sania; Alfiasari, Alfiasari; Islamiah, Nur (Universitas Mercu Buana Jakarta, 2025)
Cybersex, a component of Online Sexual Activity (OSA), is defined as engaging in sexual activities over the internet. This study aims to examine the relationship and influence of adolescent characteristics, family characteristics, self- control and peer attachment on cybersex behavior in adolescents. This study used a quantitative approach with an explanatory design on 116 adolescents in West Tanjung Jabung Regency, Jambi with a purposive sampling technique with the criteria that adolescents aged 16-18 years and often access sexual content or who have been exposed to sexual content. Data processing used Microsoft Excel software and the Statistical Package for Social Science (SPSS) program. The correlation test results show that self-control has a significant negative relationship with cybersex behavior, while peer attachment has a significant positive relationship with cybersex behavior. In addition, multiple linear regression analysis was performed to examine the simultaneous influence of self-control, peer attachment, and other relevant variables on cybersex behavior. The regression results showed a significant negative effect between self-control and length of friendship on cybersex behavior, as well as a significant positive effect of peer attachment and the duration of adolescents' gatherings with their friendship groups on cybersex behavior